Handle with care ebook - Harte, Marie (Veteran Movers, 2019)
Evan Griffith has had a hell of a day... And that was before he met the stunning, sexy woman having a meltdown. Evan Griffith has had many careers in his life. But who knew working for his family's moving company would hold just as much action as his stint in the Marine Corps? On an unforgettable job, Evan finds himself taken by a teenage conman and confronted by a woman wielding a knife—and promptly falls head over heels for her. Kenzie Sykes is doing her best to raise her little brother and keep him out of jail—all while dealing with her own broken heart that just hasn't healed. She doesn't have time for romance. He's not asking... Until he is, and she finds herself saying yes. Veteran Movers series: The Whole Package (Book 1) Smooth Moves (Book 2) Handle with Care (Book 3) Praise for Marie Harte: "With a protective alpha hero that stole my heart instantly, The Whole Package was sexy, sweet, and thoroughly satisfying."— LAUREN LAYNE , New York Times bestselling author, for The Whole Package "Marie Harte at her best! The Whole Package delivered everything I love—hot alpha, a strong woman, and amazing writing!"— DONNA GRANT , New York Times bestselling author, for The Whole Package "Terrific. I absolutely loved this story."—Night Owl Reviews, TOP PICK for The Only Thing "Another exceptionally red-hot romance by Marie Harte with a strong yet sweet hero!"—Fresh Fiction for Just the Thing